2015
DOI: 10.2215/cjn.01700215
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 Secretion and Residual Activity among Patients with Congenital Thrombotic Thrombocytopenic Purpura with and without Renal Impairment

Abstract: Background and objectives Acute renal impairment is observed in 11%-23% of patients with congenital thrombotic thrombocytopenic purpura (TTP) and deficiency of a disintegrin and metalloprotease with thrombospondin motifs 13 (ADAMTS13, a metalloprotease that cleaves von Willebrand factor [VWF] multimers), a substantial percentage of whom develop CKD during follow-up.Design, setting, participants, & measurements Here we investigated whether, in 18 patients with congenital recruited from 1996 to 2013 who fulfille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
4
14
2
Order By: Relevance
“…hemorrhagic unexplained diathesis in childhood). Similar to our case, another cTTP patient carrying a homozygous missense mutation at the same exon (p.Ile143Thr, c.428T>C) leading to low residual ADAMTS13 activity showed an early onset (at 7 years) but a detailed medical history revealed easy bruising and anemia since birth .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…hemorrhagic unexplained diathesis in childhood). Similar to our case, another cTTP patient carrying a homozygous missense mutation at the same exon (p.Ile143Thr, c.428T>C) leading to low residual ADAMTS13 activity showed an early onset (at 7 years) but a detailed medical history revealed easy bruising and anemia since birth .…”
Section: Discussionsupporting
confidence: 84%
“…The homozygous missense mutation (p.Ile143Phe) identified in our patient causes a severe secretion defect with very low residual ADAMTS13 levels, which well correlates with the early TTP onset in this patient and her relapsing course. The same homozygous mutation has been recently reported in two cTTP siblings from a consanguineous family , showing similar in vitro expression levels (i.e. severe deficiency in both antigen and activity levels).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…H234Q mutation in the ADAMTS13 gene found to be damaging through insilico methods in this study was also found to the cause of repeated renal failure in an adult patient [39]. D235Y mutation has also been studied in patients with congenital TTP [40]. Similarly, C311Y and P353L mutations in the ADAMTS13 gene have been found in patients with congenital TTP in more than one study [14,37].…”
Section: Discussionsupporting
confidence: 60%
“…Sequencing of the ADAMTS gene in patients with deep vein thrombosis identified R421C mutation [41]. G761S mutation was identified in patients with impaired renal function [40], while C908S mutation was one of 10 ADAMTS13 gene mutations in six families with congenital TTP [38].…”
Section: Discussionmentioning
confidence: 99%